Controversial Issues on the Making of Notarial Deed Containing Chained Promise (Beding Berantai) on the Freedom of Contract Principle - Tan, David (Faculty of Law, Universitas Negeri Semarang, 2019)
In carrying out the duties as a civil law notary, it is possible that they find himself/herself composing a deed containing chained promise (beding berantai). Departing from this background, it can be drawn that the formulation of the problem, among others, how is the position of chained promise (beding) in Indonesian civil law order and how is the role of civil law notary balancing legal protection for the parties in making deed containing chained promise (beding). Another controversial issue is the chained beding faced with the freedom of contract principle. The purpose of this research is to understand the position of chained promise (beding) in Indonesian civil law order and the role of civil law notary balancing legal protection for the parties in making deed containing chained promise (beding). To answer the questions, a juridical normative approach is conducted. To obtain legal materials needed, it is then carried out by searching, collecting and reviewing library materials, legislation, research results, scientific works and other written documents. Data obtained from the result of study will then be analyzed qualitatively. From the results of study, it is known that chained promise (beding berantai) is an instrument or a way to transfer rights/obligations arising from an agreement to the party that obtains rights based on a special title. Recommendations given to the stakeholders are, namely civil law notary themselves in carrying out their duties and positions so that he/she could pay more attention to the points represented in his/her product of authentic (notarial) deed.